Improving Students' Ability in Writing Recount Text by Using Topical Approach at Second Grade of Junior High School - Agnes Wiana Situmorang; Himpun Panggabean (Journal of Classroom Action Research, 2022)
This study is about improving writing recount text by using topical approach. This objective of this research is to find out whether the use of topical approach improves the students’ skill in writing recount text or not. The subject of this study was one class of the grade. Ten students of SMPN 28 Medan Johor which consisted of 30 students. The action research was conducted of july 2018. The quantitative data were taken from writing test as the instrument to find out students score. The qualitative data were taken from observation sheet, questionnaire, interview and diary notes and obseervation sheet describe the improvement of students’ skill in writing recount text was mostly improved in every test. The observation sheet and diary notes showed that the students were interested in the teaching learning process. These finding show thatthere was an improvement on the students’skill in writing recount text by using topical approach that was supported by the result, the mean score post test cycle I (75, 06) was better than mean score pre test ( 57, 43) and the mean score of post test cycle II ( 82, 03) was better than the mean score of post test cycle I. There were also positive changes in students’ behavior in learning English. During the action, the students paidgood participation to the lesson. The students were more active in joining the processof teaching and learning. Therefore, it canbe concluded that topical approach can improve the students’ skill in writing recount text. Keyword : recount text, topical approac.